Effectiveness of a SNAPPS in psychiatric residents assessed using objective structured teaching encounters: a case-control study - Lorena Pinho Feijó; Guilherme Abreu Pereira; Vitor Maia Teles Ruffini; Fernando Salvetti Valente; Renato Antunes dos Santos; Saadallah Azor Fakhouri Filho; Maria do Patrocínio Tenório Nunes; Kristopherson Lustosa Augusto (São Paulo Medical Journal, 2022)
ABSTRACT BACKGROUND: Residents play the role of teachers in almost one-quarter of their activities in residency programs. OBJECTIVE: To evaluate whether a 45-minute class using summarize, narrow, analyze, probe, plan, and select (SNAPPS) could improve psychiatry residents’ case discussion skills in diverse practical learning settings. DESIGN AND SETTING: This case-control, randomized, blinded study was conducted in a psychiatry hospital at Fortaleza-Ceará. METHODS: Using “resident as teacher” (RaT), objective structured teaching encounters (OSTEs), and SNAPPS, we conducted a study with 26 psychiatry residents. We analyzed video footage of psychiatric cases in three settings: outpatient, nursing, and emergency. An intervention was held two months later with the residents, who were then assigned to two groups: group A (lecture on SNAPPS) and group B (lecture on a topics in psychiatry). Shortly after the lectures, they were video recorded while discussing the same cases. Three blinded examiners analyzed the videos using an instrument based on the Stanford Faculty Development Program (SFDP-26). RESULTS: We found high internal consistency among external examiners and an interaction effect, group effect, and moment effect (P < 0.05). The residents who received the SNAPPS lecture scored significantly higher than their counterparts who received a traditional case presentation. CONCLUSION: This study indicates the efficacy of SNAPPS over traditional case presentation in all three settings as assessed by OSTEs and supports its implementation to improve the teaching of clinical reasoning.